Artificial Intelligence, Cybersecurity, and a Growing Ethical Dilemma - Arvin, Steven; Hendricks, Nigel; Ketel, Mohammed (Transactions on Engineering and Computing Sciences, 2025)
Currently, cybersecurity threats, particularly cyber-attacks, are a growing concern. As time goes on, it becomes increasingly challenging to hinder these attacks. Nevertheless, a new participant has entered the arena, known as artificial intelligence (AI). AI offers a way for cybersecurity experts to counteract the ever-evolving attacks. By utilizing techniques such as identifying threats and automated responses to incidents, organizations can enhance their security measures and safeguard confidential data. Despite the numerous advantages of adopting AI, it is equally important to remain vigilant about potential risks. In recent years, the rapid growth in cybersecurity threats has necessitated the development of more effective measures to protect sensitive information and systems. This paper delves into the ethical concerns of AI in cybersecurity, stressing the crucial balance between technological innovation and maintaining ethical standards.